Planetary formation and early phases - Crida, Aurélien (Comptes Rendus. Physique, 2023)
Planets form in proto-planetary disks. In this review, we describe the structure and properties of such disks, and the various phenomenons that lead to the final product: a planetary system. First, micrometre dust settles and coagulates. Then, a complex interplay between the gas and centimetre aggregates leads to efficient phenomenons such as the streaming instability and the pebble accretion. Finally, gas accretion proceeds on ten Earth mass solid cores.Once the gas disk is dissipated, giant planets may form satellites from massive rings, the terrestrial planets assemble from smaller embryos, and global dynamical instabilities give the planetary systems their final architecture.